Pengaruh Moralitas Individu, Komitmen Organisasi dan Kesesuaian Kompensasi pada Kecurangan Akuntansi - Suarniti, Ni Luh Putu Eka; Ratna Sari, Maria M. (E-Jurnal Akuntansi; Vol 30 No 2 (2020)DO - 10.24843/EJA.2020.v30.i02.p04, 2020)
Accounting fraud is an action due to the desire or encouragement to use the opportunity so as to manipulate accounting of financial statements, corruption or misappropriation of assets. Research aims to determine the influence of individual morality, organizational commitment and conformity of compensation on accounting fraud in the LPD of Mengwi sub-district. The sampling method is using the purposive sampling technique. The data collection method is permormed using questionnaires and questionnaires returned are 194 questionnaires. The data analysis technique used is multiple linear regression. Based on the results of the tests, individual morality, organizational commitment and compensation conformity have negative affect on accounting fraud. Keywords: Individual Morality; Organizational Commitment; Compensation Conformity; Accounting Fraud.